Economic Impact of Tyson Foods' Plant Closure in Northeast Florida, 2002 - Tom Stevens; Alan Hodges; David Mulkey (EDIS)
This is EDIS document FE369, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published January 2003.